Sample size determination and power - Ryan, Thomas P., 1945- (John Wiley & Sons, 2013)
Featuring a comprehensive approach to sample size determination for general statistical use, this book uniquely blends applications from a variety of fields including statistics, biostatistics, the health sciences, and engineering. Topical coverage includes: hypothesis testing concepts and issues; confidence intervals; methods of determining sample sizes; means and variances; proportions and rates; regression methods and correlation; experimental designs; clinical trials; quality improvement; survival analysis and reliability; and nonparametric methods.